Analisis Kesalahan Berbahasa pada Karangan Siswa Kelas VI Sekolah Dasar - Dewi, Atika; Darmuki, Agus; Fathurohman, Irfai (Diskursus: Jurnal Pendidikan Bahasa Indonesia, 2025)
Language skills play an important role in the process of thinking and expressing ideas. One of the language skills taught since elementary school is writing skills, especially creative writing in the form of narrative essays. However, in practice, there are still many language errors in the students’ essays. This study aims to analyze the forms of language errors in the realm of spelling errors in the narrative essays of grade VI students of SDN Soneyan 02. The research uses a qualitative descriptive approach using document analysis techniques. Data were obtained from 23 narrative essays which were analyzed through 4 stages, collection of data containing errors, identification of errors, description of errors, and explanation of errors. The results showed that the results of students’ narrative essays still showed errors in spelling rules that were repetitive and systematic. These errors include the use of capital letters, the writing of prepositions, the use of punctuation marks, and the writing of loanwords. Efforts are needed to overcome errors and strengthen students’ understanding of correct language rules in order to improve students’ writing skills appropriately and consistently.